1977
DOI: 10.1177/030089167706300510
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin Alone and in Combination with Radiotherapy in the Treatment of Inoperable Esophageal Cancer

Abstract: Thirty-three patients with inoperable esophageal cancer were treated in a randomized study. There were 24 squamous cell, 2 anaplastic, 4 unclassified, and 3 adenocarcinomas. Eighteen patients were treated with 6 cycles of adriamycin with a 3 week rest period between cycles. Adriamycin was administered in doses of 40 mg/m2 body surface daily for 2 days during each cycle. The other group of 15 patients were treated with both adriamycin and radiation. The tumor was irradiated with speed electrons (4500–5200 rads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Kolaric and coworkers compared efficacy of bleomycin, Adriamycin ® , and bleomycin/Adriamycin ® combination alone and each in combination with radiotherapy. 5,6,21 The multimodality regimens gave overall and complete response rates superior to those of chemotherapy-alone arms in these trials. The bleomycin/Adriamycin ® two-drug regimen disappointingly gave no advantage over results obtained by bleomycin or Adriamycin ® in combination with radiotherapy.…”
Section: Combined Modality Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Kolaric and coworkers compared efficacy of bleomycin, Adriamycin ® , and bleomycin/Adriamycin ® combination alone and each in combination with radiotherapy. 5,6,21 The multimodality regimens gave overall and complete response rates superior to those of chemotherapy-alone arms in these trials. The bleomycin/Adriamycin ® two-drug regimen disappointingly gave no advantage over results obtained by bleomycin or Adriamycin ® in combination with radiotherapy.…”
Section: Combined Modality Treatmentmentioning
confidence: 97%
“…Kolaric, et al reported one complete and five partial responses in 18 patients. 6 The Eastern Cooperative Oncology Group compared the activity of Adriamycin ® with those of methotrexate and 5-fiuorouracil (5-FU) in a randomized study. 7 Responses were seen in one of 18 (five percent), two of 27 (seven percent), and four of 26 (15 percent Data on efficacy of new antitumor agents against esophageal cancer are summarized in Table 1.…”
Section: Single-agent Chemotherapymentioning
confidence: 99%
“…Another type of comparison has been made in two randomized trials by Kolaric et al (38,123). CT alone has been compared with CT (doxorubicin + bleomycin or doxorubicin alone) given concurrent with RT showing significantly better response rates when combined therapy was used (38,123).…”
Section: Chemoradiotherapy Without Surgerymentioning
confidence: 99%
“…CT alone has been compared with CT (doxorubicin + bleomycin or doxorubicin alone) given concurrent with RT showing significantly better response rates when combined therapy was used (38,123). In a first study the response rate was 33% vs 60% for doxorubicin and doxorubicin + RT (45-52 Gy, 2 Gy/fraction) respectively (123) and in a second study doxorubicin + bleomycin gave a response rate of 19% and doxorubicin + bleomycin + RT (36-40 Gy, 2 Gy/fraction) a 60% response rate (38).…”
Section: Chemoradiotherapy Without Surgerymentioning
confidence: 99%
“…Doxorubicin has shown activity in esophageal and gastric cancer [1][2][3], while in pancreatic and colorectal cancer activity appears low [4,5], Epirubicin is one of a series of new anthracycline antibiotics synthesized in an attempt to identify agents with a superior therapeutic index to the parent com pound doxorubicin. Pharmacokinetics of the two drugs are different and despite the chemical similarity with doxorubicin, epirubicin may have different biologic properties.…”
Section: Introductionmentioning
confidence: 99%